Epitope-specific regulation of memory programming by differential duration of antigen presentation to influenza-specific CD8+ T cells - Ballesteros-Tato, André (Immunity, 2014)
Memory CD8(+) T cells are programmed during the primary response for robust secondary responsiveness. Here we show that CD8(+) T cells responding to different epitopes of influenza virus received qualitatively different signals during the primary response that altered their secondary responsiveness. Nucleoprotein (NP)-specific CD8(+) T cells encountered antigen on CD40-licensed, CD70-expressing, CD103(−)CD11b(hi) dendritic cells (DCs) at later times in the primary response. As a consequence, they maintained CD25 expression and responded to interleukin-2 (IL-2) and CD27, which together programed their robust secondary proliferative capacity and interferon-γ (IFN-γ)-producing ability. In contrast, polymerase (PA)-specific CD8(+) T cells did not encounter antigen-bearing, CD40-activated DCs at later times in the primary response, did not receive CD27 and CD25 signals and were not programmed to become memory CD8(+) T cells with strong proliferative and cytokine-producing ability. As a result, CD8(+) T cells responding to abundant antigens, like NP, dominated the secondary response.